Strengthening Discipline and English Proficiency: EFL Preservice Teachers' Perspectives on Reciting Qur'an with English Translation - Zulfa Nabila; Eka Fanti Sulistiyaningsih; Atik Muhimatun Asroriyah; Hastri Firharmawan (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study explores EFL preservice teachers' perspectives on reciting the Qur'an with English translation as a strategy to strengthen discipline and English proficiency. Descriptive mixed methods was employed at the English Education Department of UMNU Kebumen, involving 47 preservice teachers from second and fourth semesters. Data were collected through questionnaires, semi-structured interviews, observations, and documentation over one semester. The findings revealed that students held highly positive perspectives, perceiving the practice as an educational consequence rather than punishment. The activity effectively reduced tardiness frequency, enhanced students' awareness of punctuality, and facilitated internalization of discipline as personal value. Regarding language development, students reported perceived improvements in vocabulary acquisition, pronunciation skills, and recognition of Islamic-English lexical equivalents. The integration of religious values made English learning more meaningful and identity-relevant. All interviewed students expressed intention to implement similar approaches in their future teaching careers with contextual adaptations. This study contributes to the theoretical frameworks of Liberating Discipline Pedagogy, Sociocultural Theory, and CLIL in Pre-Service Teacher Education by demonstrating how religious texts can function as mediational tools for simultaneous behavioral regulation and perceived language development. The findings offer practical implications for English teachers and curriculum developers in Islamic educational contexts.